Shape characteristics of the aggregates formed by amphiphilic stars in water: dissipative particle dynamics study - Kalyuzhnyi, O.Y.; Ilnytskyi, J.M.; C. von Ferber (Condensed Matter Physics, 2017)
We study the effect of the molecular architecture of amphiphilic star polymers on the shape of aggregates they form in water. Both solute and solvent are considered at a coarse-grained level by means of dissipative particle dynamics simulations. Four different molecular architectures are considered: the miktoarm star, two different diblock stars and a group of linear diblock copolymers, all of the same composition and molecular weight. Aggregation is started from a closely packed bunch of Na molecules immersed into water. In most cases, a single aggregate is observed as a result of equilibration, and its shape characteristics are studied depending on the aggregation number Na. Four types of aggregate shape are observed: spherical, rod-like and disc-like micelle and a spherical vesicle. We estimate “phase boundaries” between these shapes depending on the molecular architecture. Sharp transitions between aspherical micelle and a vesicle are found in most cases. The pretransition region shows large amplitude oscillations of the shape characteristics with the oscillation frequency strongly dependent on the molecular architecture. В роботi вивчається ефект молекулярної архiтектури амфiфiльних зiркових полiмерiв на форму агрегатiв, якi вони формують у водi. Полiмери та вода описуються на мезоскопiчному рiвнi, використовуючи метод дисипативної динамiки. Розглянутi чотири молекулярнi архiтектури: мiктозiрки, два типи дiблок-зiрок i група лiнiйних дiблок кополiмерiв, усi з однаковою композицiєю та молекулярною масою. Ми розглядаємо початкову конфiгурацiю у виглядi густого клубка iз Na молекул, помiщеного у воду. В рiвноважному станi формується агрегат, характеристики форми якого дослiджуються при рiзних значеннях Na. Знайдено чотири форми агрегатiв: сферична, стержнеподiбна та дископодiбна мiцелла та сферична весiкула. Оцiненi “фазовi границi” мiж цими формами залежно вiд молекулярної архiтектури. У бiльшостi випадкiв знайдено рiзкий перехiд мiж асферичною мiцеллою та весiкулою. Передперехiдна область характеризується осциляцiями властивостей форми iз великою амплiтудою, частота яких суттєво залежить вiд молекулярної архiтектури.